Phonological Interference of the Bugis Dialect on the Indonesian Language in the Bambaloka Community in Baras District - Fika; Moh Tahir; Juniati; Yunidar; Ulfah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to describe the form of interference of the Bugis dialect in Indonesian speech in the Bambaloka community, Baras District, through a descriptive qualitative approach with data in the form of spontaneous speech collected using listening, recording, and recording techniques in the context of informal communication, and analyzed using the Miles and Huberman model. The results of the study revealed that the interference that occurred was concentrated in one form, namely phonological interference, which included 13 specific patterns including the change of the phonemes /m/ and /n/ to /ng/ at the end of the word, modification of the vowels /o/ and /e/ at the end position, the elimination of the consonants /h/, /t/, /p/, and /k/ which are prevalent accompanied by the addition of the particles /mi/ and /ji/ typical of the Bugis dialect,  As well as the pattern of contraction, assimilation, change of the liquid phoneme /r/, and simplification of consonant clusters as seen in the realization of the word has become sudami and not become didaji. This phenomenon takes place systematically because the Bambaloka people are a bilingual community that makes the Bugis dialect their mother tongue, so that the phonological system of the first language is consistently carried over into their Indonesian speech. This finding has practical significance as the basis for designing an Indonesian language learning strategy that is more contextual and responsive to the linguistic characteristics of bilingual communities, especially for speaking communities living in a language contact situation between regional languages and Indonesian.